(untitled) (International Journal of Built Environment and Sustainability, 2022)
Literature studies reveal that mankind spends 90% of their life indoors. The current COVID 19, pandemic situation has capped the socialization among the people due to diverse reasons. This situation has questioned as well as challenged the age-old practices and standards that have been adopted in designing spaces for various functions. This study reinstates the need to maintain the health of the occupants especially in corporate offices. Achieving the users’ health and wellness that include some aspects of thermal comfort is challenging. The aim is to study, understand and achieve the key parameters that revolves around ‘health’ and ‘wellness’ of the occupants in corporate spaces that is expected to be occupied partially even during challenging situations. Exploratory methodology is adopted to identify and consolidate such parameters in this article. The data was collected from secondary resources such as ‘Well Building Standard’ by the International Well Building Institute, ‘Indian Green Building rating system’, ‘pandemic guidelines’ and ‘research articles’. It is observed that parameters such as ‘adequate and appropriate ventilation’, ‘indoor and native plants’ and ‘relative humidity’ need to be considered while facilitating the functioning of corporate spaces with minimum occupancy in situations which demand physical and social distancing. The role and the impacts of these parameters need to be explored in real time contexts.